Suplementasi Tepung Jangkrik Sebagai Sumber Protein Pengaruhnya Terhadap Kinerja Burung Puyuh (Coturnix coturnix japonica) - Panjaitan, Imelda; Sofiana, Anjar; Priabudiman, Yadi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2012)
This research aims to study and determine the effect of crickets flour supplementation of feed on performance of quail (Coturnix coturnix japonica). The material used is Day Old Quail (DOQ) were 70 individuals (35 males and 35 females), commercial rations for laying hens and cricketsÂ  flour. Experiments designed to completely randomized design factorial 2x5 pattern. The first factor gender (male and female), the second factor adding crickets flourÂ  into a commercial ration (0%, 2%, 4%, 6% and 8% of the ration). Each treatment was repeated 7 times. Variables observed in this study is consumption, body weight gain, conversion and carcass percentage. Data were analyzed using the Fingerprint Variety of RAL factorial ANOVA. Further test of the simple effect or primary conducted using Duncan's Multiple Range Test (DMRT). The results showed that supplementation of crickets flour in feed did not affect on feed consumption, but it influenced on body weight gain, feed conversion ratio and carcass percentage of male and female Japanese quail.